Praktik Performatif al-Qur’an dalam Tradisi Yasinan Nahdliyin: Suatu Kajian Living Qur’an - M. Fuad Hasan; Mansur Hidayat; Anis Fitriyah (Kuras Institute, 2025)
This study investigates the Yasinan ritual among the Nahdliyin community in Margodadi, Metro Selatan, through a Living Qur’an approach combined with sociological and hermeneutical analysis. Using ethnographic methods—participant observation over eight weeks and in-depth interviews with 12 practitioners—the research examines how Qur’anic recitations are enacted, embodied, and socially institutionalized. Findings show that Yasinan functions as a performative tafsīr in which meanings of the Qur’an are materialized through ritual sequences involving tawassul, communal recitation, and collective supplication. The ritual generates layered significations: spiritual (seeking divine proximity and protection), social (solidarity, role distribution, and moral bonding), and cultural (integration of Qur’anic text with Javanese symbolic expressions). The study contributes to Living Qur’an scholarship by demonstrating how local epistemologies shape Qur’anic meaning-making beyond textual exegesis, offering a model for analyzing the Qur’an as a socially enacted and ritually embodied text.